Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

Electronically and catalytically functional carbon cloth as a permeable and flexible counter electrode for dye sensitized solar cell - Tathavadekar, Mukta; Biswal, Mandakini; Agarkar, Shruti A.; Giribabu, Lingamallu; Ogale, Satishchandra (Electrochimica Acta, 2014)
In this work we demonstrate that a conducting carbon cloth obtained by one-step pyrolysis of easily available cellulose fabric competes favorably with the commonly employed expensive platinum/FTO system as a counter electrode for dye sensitized solar cell (DSSC). In view of the low carbonization temperature (1000 degrees C) which forbids full graphitization, the nature of carbon in this case is represented by topologically randomly assembled nanoscale graphene units (turbostratic carbon). This morphology has high density of edge states and oxygen containing surface groups rendering multitude of catalytic sites for the reduction of I-3(-). Moreover the cloth is permeable to the dye and/or liquid electrolyte and its absorption properties also help retain the electrolyte. A fairly high efficiency of 5.8% is achieved using such cloth as a counter electrode as against 7% with the conventional Pt/FTO system. Moreover, the permeable property of the cloth eliminates a complete step of drilling hard TCO substrates for final dispensing of electrolyte into the device and the sealing process is also facile. In fact even the dye can be dispensed through the cloth. Finally, the flexibility of the carbon cloth can adapt easily to flexible/wearable DSSC designs. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: conducting carbon cloth; counter electrode; DSSC; without drilling

Large scale synthesis of graphene quantum dots (GQDs) from waste biomass and their use as an efficient and selective photoluminescence on-off-on probe for Ag+ ions - Suryawanshi, Anil; Biswal, Mandakini; Mhamane, Dattakumar; Gokhale, Rohan; Patil, Shankar; Guin, Debanjan; Ogale, Satishchandra (Nanoscale, 2014)
Graphene quantum dots (GQDs) are synthesized from bio-waste and are further modified to produce amine-terminated GQDs (Am-GQDs) which have higher dispersibility and photoluminescence intensity than those of GQDs. A strong fluorescence quenching of Am-GQDs (switch-off) is observed for a number of metal ions, but only for the Ag+ ions is the original fluorescence regenerated (switch-on) upon addition of L-cysteine.

Water electrolysis with a conducting carbon cloth: subthreshold hydrogen generation and superthreshold carbon quantum dot formation - Biswal, Mandakini; Deshpande, Aparna; Kelkar, Sarika; Ogale, Satishchandra (ChemSusChem, 2014)
A conducting carbon cloth, which has an interesting turbostratic microstructure and functional groups that are distinctly different from other ordered forms of carbon, such as graphite, graphene, and carbon nanotubes, was synthesized by a simple one-step pyrolysis of cellulose fabric. This turbostratic disorder and surface chemical functionalities had interesting consequences for water splitting and hydrogen generation when such a cloth was used as an electrode in the alkaline electrolysis process. Importantly, this work also gives a new twist to carbon-assisted electrolysis. During electrolysis, the active sites in the carbon cloth allow slow oxidation of its surface to transform the surface groups from COH to COOH and so forth at a voltage as low as 0.2V in a two-electrode system, along with platinum as the cathode, instead of 1.23V (plus overpotential), which is required for platinum, steel, or even graphite anodes. The quantity of subthreshold hydrogen evolved was 24mLcm(-2)h(-1) at 1V. Interestingly, at a superthreshold potential (>1.23V+overpotential), another remarkable phenomenon was found. At such voltages, along with the high rate and quantity of hydrogen evolution, rapid exfoliation of the tiny nanoscale (5-7nm) units of carbon quantum dots (CQDs) are found in copious amounts due to an enhanced oxidation rate. These CQDs show bright-blue fluorescence under UV light.
Keywords: Carbon; electrolysis; Hydrogen; photoluminescence; quantum dots